Laboratory life the construction of scientific facts - Latour, Bruno (Princeton Princeton University Press, 1986)
This highly original work presents laboratory science in a deliberately skeptical way: as an anthropological approach to the culture of the scientist. Drawing on recent work in literary criticism, the authors study how the social world of the laboratory produces papers and other "texts,"' and how the scientific vision of reality becomes that set of statements considered, for the time being, too expensive to change. The book is based on field work done by Bruno Latour in Roger Guillemin's laboratory at the Salk Institute and provides an important link between the sociology of modern sciences and laboratory studies in the history of science.
Includes bibliographies and index.
Keywords: Biology--Research.